Provisión de servicios de salud pública y su influencia en el nivel de satisfacción de los usuarios, cantón Quevedo, año 2023 - León Macias, Lilia Vanessa (2023)
The objective of this thesis is to evaluate the relationship between the provision of public health services and the satisfaction of users who attend health centers in the urban area of Quevedo. Through this objective, it is planned to determine the level of user satisfaction in relation to the quality of public health services offered to the target population segment. The methodology used for this thesis was a quantitative study that collected data on the quality of health services, user satisfaction and other factors that could influence this relationship. The research sample was made up of 384 users of the health centers in the urban area of Quevedo, the survey technique was used, the questions were measured using the 5-point Likert scale, then the information collected was tabulated. in Excel and graphed with the SPSS V25 statistical software. The results showed that users are completely dissatisfied with the accessibility of services; which is reflected in timely care, quality, personalized attention, the information provided, the acquisition of medications and the comfort of the facilities. Therefore, the results indicate the urgent need to improve the quality of public health services in Quevedo. Hence, the authorities of the Ministry of Public Health must take measures to guarantee that users receive the care they need and deserve.